ItMatters: Optimization of an online intervention to prevent sexually transmitted infections in college students. Issue 4 (19th May 2022) - Wyrick, David L.; Tanner, Amanda E.; Milroy, Jeffrey J.; Guastaferro, Kate; Bhandari, Sandesh; Kugler, Kari C.; Thorpe, Shemeka; Ware, Samuella; Miller, Alicia M.; Collins, Linda M.
Abstract: Objective To describe an iterative approach to developing an online intervention targeting the intersection of alcohol use and sexual behaviors among first year college students. Methods and Participants: Using the multiphase optimization strategy (MOST), we conducted two iterative optimization trials to: (1) identify candidate intervention components (i.e., descriptive norms, injunctive norms, outcome expectancies, perceived benefits of protective behavioral strategies, and self-efficacy to use strategies); (2) revise components; and (3) identify the optimized intervention. Participants were first year college students at six geographically diverse universities (optimization trial 1 N = 5, 880; optimization trial 2 N = 3, 551) Results: For both optimization trials, the results indicated that only descriptive and injunctive norms produced a significant effect (p<.05). Conclusions: The iterative process of MOST allowed us to develop an optimized intervention which is an essential tool to maximize intervention effectiveness and efficiency to improve uptake, sustainability, and public health impact.